Cuadro clínico experimental de un terreno inoculado con Escherichia Coli K99+ - Zurita A., Livio; Montes O., Gustavo; Smith S., Pedro; Muhlenbrock Z., Horacio; Aguilera S., Hernán (Monografías de Medicina Veterinaria, 1990)
-